Anesthetic efficacy of Mentha piperita and Mentha spicata essential oils on rainbow trout (Oncorhynchus mykiss) - Metin, Secil; Ozdikyar, Onur; Telci, Isa (Journal of Fisheries, 2025)
In the present study, anesthetic effects of Mentha piperita and Mentha spicata essential oils were investigated on rainbow trout. For this purpose, five treatments of the essential oils (50, 100, 200, 300 and 500 mg L–1 concentrations) and one control (2-phenoxyethanol; 0.3 ml L–1 concentration) have been used for rainbow trout (Oncorhynchus mykiss; mean weight of 15 g). In addition, the mean lethal doses (10 minutes LC50 concentration) of the essential oils were also determined. Mentha piperita and M. spicata essential oils at 200, 300 and 500 mg L–1 doses showed better anaesthetic effect than control (p < 0 .05). The ideal anesthetic dose of each essential oil was 200 mg L–1 (p < 0.05). At this concentration, deep anesthesia (Stage IV) induction time for M. piperita and M. spicata on rainbow trout were found as 169.66 s and 65.0 s, respectively. The recovery times at 200 mg L–1 concentration were 188.0 s for M. piperita and 65.33 s for M. spicata. The lethal dose of both essential oils in fish was 150 mg L–1. This study suggests that the essential oils of M. piperita and M. spicata are both effective anesthetic agents for rainbow trout.